Protect 'our only home' - Abd Razak, Dzulkifli (2005)
GRIM headlines appeared in the media last week: Polar bears and seals may be extinct within 20 years (NST, Jan 31); Global warning twice as bad (NST, Jan 26). Global warming near point of no return (NST, Jan 25). At the World Economic Conference in Davos, Britain's Prime Minister Tony Blair during a keynote address last week reportedly reminded the world of the situation in Africa: 300 million Africans lack safe water, 3,000 African children under the age of five die every year from malaria and 6,000 Africans die daily of AIDS (NST. Jan 28). For many of us, the response would be simply what have polar bears, seals and Africa got to do with us? At a glance it may not be much, except that we belong to the same globe, meaning at some point or other we will all be affected.